A Cotton Annexin Affects Fiber Elongation and Secondary Cell Wall Biosynthesis Associated with Ca2+ Influx, ROS Homeostasis, and Actin Filament Reorganization. Issue 3 (2nd June 2016) - Zhang, Feng; Jin, Xuanxiang; Wang, Like; Li, Shufen; Wu, Shuang; Cheng, Chaoze; Zhang, Tianzhen; Guo, Wangzhen
Abstract : GhFAnnxA promotes Ca 2+ influx, leading to the production of ROS and, together with F-actin activity, affecting fiber development. Abstract: Annexins play pivotal roles in a variety of cellular processes as well as in fiber development; however, the functional mechanisms of their activities are unclear. Here, an annexin gene that is preferentially expressed in fibers, GhFAnnxA, was found to be significantly associated with various cotton ( Gossypium hirsutum ) fiber traits. Transgenic analysis demonstrated that GhFAnnxA affected cotton fiber elongation and was involved in secondary cell wall (SCW ) biosynthesis. Functional studies demonstrated that GhFAnnxA may act as a Ca 2+ conductance regulator and that reactive oxygen species (ROS ) produced by Rbohs in a Ca 2+ -dependent manner may determine fiber elongation caused by elevated intracellular turgor and cell wall loosening. However, excessive hydrogen peroxide (H2 O2 ) inhibited cotton fiber elongation in vitro. We speculate that a positive feedback loop involving ROS and Ca 2+ is regulated by GhCDPK1 and regulates fiber cell elongation. Furthermore, the convergence of actin filaments is altered by their interaction with GhFAnnxA, and this also may contribute to fiber elongation. Moreover, GhFAnnxA may affect SCW biosynthesis through changes in cell wall components caused by an increase in H2 O2 levels. These results not only provide new insights into the signaling pathways of GhFAnnxA in fiber development but also clarify the role of ROS in fiber development.